PHYSICAL THERAPY FOR RUPTURE OF ACHILLES TENDON (REVIEW OF LITERATURE SOURCES) (Physical Culture and Sport: Scientific Perspective, 2024)
A ruptured Achilles tendon is a serious injury that often occurs as a result of sudden jerky movements such as jumping, running, or rapid changes of direction. Especially often, such injuries occur in athletes who regularly engage in physical activity. The incidence of such cases varies from 11 to 37 per 100,000 population, which indicates a relative rarity of the injury in the general population, but in the sports environment these figures are much higher. According to research from the Rocky Mountain Foot & Ankle Orthopedic Clinic (Utah, USA), the number of Achilles tendon ruptures among athletes is increasing every year and ranges from 6,000 to 18,000 cases per 100,000 athletes. About 25% of athletes experience an Achilles tendon injury during their lifetime, which indicates a high risk of this problem in active people.Physical therapy plays a key role in the recovery process after Achilles tendon injuries. The main goal is not only to restore the function of the tendon, but also to ensure the proper functioning of the muscles surrounding it. This is necessary to avoid repeated injuries and ensure full motor activity. Rehabilitation programs designed for such patients often include muscle-strengthening exercises, stretching, proprioceptive training, and gradually increasing the load on the affected limb. The success of recovery depends on an individual approach to each patient, taking into account the degree of damage and physical capabilities.The purpose of research in this field is to generalize recommendations on effective rehabilitation methods after rupture of the Achilles tendon. The used research methods include analysis, comparison, induction, deduction and generalization of scientific and methodological literature. Studies confirm that timely and adequate rehabilitation significantly affects the recovery of patients and allows them to return to active life faster.In general, in connection with the aging of the population and the growing popularity of an active lifestyle, the number of cases of rupture of the Achilles tendon is constantly increasing, and therefore the issue of effective treatment and rapid rehabilitation of patients becomes even more important.
Keywords: physical therapy; rupture of the Achilles tendon; injury; conservative treatment; surgical intervention